Membuka Otoritas Pintu Ijtihad Perspektif Paradigm Based on Maqashid Syari’ah - Zamroji, Muhammad (AR ROSYAD: Jurnal Keislaman dan Sosial Humaniora, 2024)
There are two types of corruption faced by Islam, which led to the stagnation of the creativity of ijtihad of the mujtahids, so that the lack of Islamic legal products, such as: First, churafat, including idolatry, which is the height of corruption, shamanism, predictions about the arrival of good and bad things, magic, gambling and others. Secondly, the suppression of freedom of thought, which leads the mind to take a policy from an essence that is not in accordance with the correct position of the Dzan. This phenomenon has plagued the thinking of Muslims in recent decades. The purpose of this research is to explain freedom of thought (tahrir al-aqli) as the most basic manifestation of the preservation of reason (hifzu 'aql). Freedom of thought is one of the efforts to preserve the mind from the side of its preservation, which is part of the concept of the basic structure of Maqashid Shari'ah, which revolves around the basic paradigm of benefit (Paradigm Based On Maqashid Shari'ah). This research is a literature study using descriptive analysis method through maqasid al-shari'ah approach. The results of this discussion show that the solution to break the stagnation of thought in the Islamic world, so that the door of Ijtihad is reopened, is to promote and demonstrate freedom of thought. All forms of restriction of thought that prevent critical thinking must begin to be abandoned. By maximising the potential of freedom of thought, which is the movement of the intellect to find the essence of something, it will be able to understand the divine treasure and reveal the shar'i laws to enforce the Shari'a according to what the Shari'a wants